Images are not and should not ever be type specimens: a rebuttal to Garraffoni & Freitas - Rogers, D. Christopher; Ahyong, Shane T.; Boyko, Christopher B.; D’acoz, Cédric D’udekem (Zootaxa, 2017)
Note. This original form of this rebuttal was submitted to Science on 3 March 2017 (limited to 300 words as per Science editorial policy) but rejected on 13 March 2017. Herein, we elaborate on our original Science submission in order to more fully address the issue without the length limitations. This rebuttal is followed by the list of the signatories who supported our original submission.